Adalékok a zsidó népesség társadalmi-gazdasági szerepéhez a dualizmuskori Bánságban - Kókai, Sándor (Közép-Európai Közlemények, 2015)
The Jewish population of Banat rate lower than the Hungarian average in the total population. During the 1870 census 15734 Jewish religion, in the 1910 census 20643 people lived in the Jewish Banat. Economic, cultural and political significance of the Jewish population in the Banat population is much higher, than the numerical ratio. Social inclusion and emancipation with respect no significant differences in national trends, however, the economic weight –particularly in the agricultural and industrial context –an order of magnitude smaller than the Banat. The reasons only one, but not decisive in the lower numerical ratio, much more important that the structure of the Banat economy is different from the national average. The Banat good quality soil business estates are less financially strong middle hired out their owners, but also for large estates over a thousand acres of rental rates are also below the national average in common. Belonging to the foreign operation and the unfolding of modern manufacturing industry (STEG Rt.). In addition to industry-formation Temesvár only loosely can join the Jews, but where major economic power and political and social power is concentrated in their hands. Surprisingly, the middle of 19th century paramount agricultural produce trading centers (eg. Törökbecse, Törökkanizsa, Csák etc) are not concentrated in large Jewish population and material resources. Economic position of the Jews in Banat indirectly shows the number of synagogues, which in turn is experiencing interesting anomalies. The integration of Jewish communities, accumulation of wealth, and last but not least shows faith in the future, that the Banat 12 synagogue was built during the period 1880–1913.